Hybrid approach for urban hilly catchment runoff modelling and prediction of pollutant loads. Issue 15 (17th November 2020) - Kumar, Sumant; Ghosh, Narayan C.; Kazmi, A. A.; Jain, Sharad K.; Kumar, Vinod; Rajpal, Ankur
ABSTRACT: This paper presents a hybrid approach for stormwater runoff modelling and pollutant load estimation in a hilly catchment. The stormwater runoff hydrograph was simulated by developing a conceptual hybrid model (HM) using transfer function. Model parameters were estimated by non-linear optimization. The simulated runoff hydrographs showed an excellent match with the observed data. Next, a relationship was developed between runoff and pollutant load and the developed relationship was used for estimation of pollutant load. A novelty of this hybrid approach is that it could bring out a generic HM. By using the derived model, the pollutant load was successfully predicted from simulated runoff (R 2 > 0.75) by considering rainfall as the only input. In addition, assessment, characterization and analysis of the first flush of urban runoff also form part of the study. The HM was tested and validated by applying it to 25 storm events monitored during two monsoon seasons in the Nainital Lake catchment (approx. 1900 m a.m.s.l.), India.